Vocational support in mental health service delivery in Australia. (10th November 2019) - Petrakis, Melissa; Stirling, Yolande; Higgins, Kate
Abstract: Background: Individuals experiencing severe and persistent mental illness report a desire to gain and sustain work. Individual Placement and Support (IPS) is an evidence-based approach to vocational rehabilitation to support competitive employment outcomes. Aim/Objective: This study aimed to evaluate whether a joint-governance management partnership, between a clinical adult mental health and an employment service, could deliver a sustained IPS program in Australia. Materials and Method: The methodology entailed a Clinical Data Mining approach, to examine records from seven years of implementation of IPS in one setting within an Australian public mental health service context. Results/Findings: Despite the prevalence of schizophrenia spectrum diagnoses and an older mean age (39 years), indicating that a large proportion of the cohort had experienced serious mental illness for over twenty years, findings were that 46.3% of participants achieved employment. Conclusions: This is an excellent result and is comparable to the only randomised control trial, with adult services, in the Australian context, which found a 42.5% employment rate possible under IPS compared with just 23.5% with referral to external employment services. Significance: More extensive trialling of IPS across clinical services is required, in Australia and internationally, including fidelity protocols, for knowledge translation to be achieved.